PENDEKATAN KONSELING ISLAM DALAM MENGATASI PROBLEMA PSIKOLOGIS MASYARAKAT - Akhmadi, Agus (Balai Diklat Keagamaan Surabaya, 2016)
Restlessness and anxi ety problem of modern soci ety comes fromindividual psychological (internal factor) and from political and socialfactors such as di scriminati on and inj usti ce. To overcome thoseproblems, i mpl ementi ng psychodynamic theory, behavi ori sm,humanism and multiculturalism are not enough. We are introduced tothe fifth approach, that is, Islamic approach. The approach which is basedon the belief, religious knowledge, and worship practices becomes theguidelines, techniques and destination Islamic counseling. The Islamiccounseling is aimed at preventive, curative, rehabilitative development,using spiritual methods which are based on the counselee. Spiritualmethods with techniques of spiritual practice, establish compassion,and reflection al Qudwah al-hasanah. Counselee-centered method is doneby discussion and advice according to the counselees’ interests and values.A counselee is free to choose, plan, decide the behavior and values thatare meaningful to him.